An Analysis of The Perceived Factors Impacting Employee Satisfaction and Retention in Saudi Arabia’s Higher Education Sector - Alharthey , Abdullah Mulfi; Leong, Yee Choy; Said, Mohd Fuaad; Chong, Choo Wei (Advances in Social Sciences Research Journal, 2022)
The purpose of the study is to examine the factors that are perceived to have an impact on employee satisfaction and retention. This study employed a survey approach in order to gain the respondents' perceptions of the study. The target respondents of this study are academicians in the educational sector in Saudi Arabia. The source of the sampling based on the Saudi Ministry of Higher Education. A total of 384 respondents participated in this study, and the collection of the data was based on a stratified probability sampling technique. To address the research objectives, the study employed PLS-SEM to test the hypotheses of the study. The study has found that work engagement, co-worker relationships, and a supportive work environment are key to employee satisfaction in the educational sector in Saudi Arabia. Meanwhile, the working environment, perceived organizational support, and a supportive work environment are key to employee retention.